Strategi Pengembangan Obyek Wisata Taman Siring Laut di Kabupaten Kotabaru Kalsel - Baharullah, Baharullah; Rahmini, Noor (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine (1) the creative economic potential that can be developed at the Kotabaru Siring Laut Park, (2) the potential attractions that can be developed at the Siring Laut Park tourism object in Kotabaru Regency, (3) what internal factors are the strengths and weaknesses in the development of sea siring tourism in Kotabaru district, (4) what external factors are the opportunities and threats to the development of sea siring tourism in Kotabaru district and (5) what is the strategy in developing the right siring sea park tourism in Kotabaru Regency. The results showed that development of the most appropriate strategy was the S-O strategy (1) Increasing culinary tourism attractions is one of the proper steps that the government must take because many tourists who visit with their families not only enjoy the beauty of the tour but one of the reasons they visit is to enjoy various kinds of dishes are provided that can be enjoyed when with family, (2) maintain and increase the perception of tourists to visit this tourist attraction because the tourist location is very strategic and easy to reach and has a comfortable atmosphere with beautiful panoramas.